Behaviours and Beliefs Related to Whistleblowing Against Doping in Sport: A Cross-National Study - Bondarev, Dmitriy; Barkoukis, Vassilis; Lazuras, Lambros; Bochaver, Konstantin; Oudra, Despoina; Theodorou, Nikolaos (Frontiers in Psychology, 2022)
Background: Whistleblowing has been recognized as an important deterrent of doping in elite competitive sport. The present study examined athletes’ knowledge of external whistblowing channels and on how and where to report doping misconduct, perceived trust in different whistleblowing reporting channels, whistleblowing behaviour and athletes' reasons for reporting (or not) doping misconduct. Methods: Athletes from Greece (n=480), Russian Federation (n=512) and the United Kingdom (n=171) completed a structured questionnaire on demographics, knowledge of different whistleblowing channels, perceived trust in internal and external whistleblowing channels, past whistblowing behaviour and reasons for reporting (or not) doping misconduct. Results: The British athletes reported greater awareness of whistleblowing reporting channels (e.g., WADA's Speak Up and IOC's reporting platform) than did athletes from Greece (all p<0.001) and Russia (p=0.07, and p=0.012) respectively. However, British athletes reported the lowest scores on knowledge of how and where to report doping misconduct, as compared to athletes from Greece and Russia. The majority of respondents reported greater trust to their coach or a club manager than to other whistleblowing channels, however, responses regarding other channels varied by country. Among athletes who detected doping miscount 36 % of athletes did not report it, while 23 % reported it. Reasons for and not reporting doping misconduct were collated in eight themes by thematic analysis. Conclusion: Athletes showed low awareness of external whistblowing channels and they predominantly trusted internal whistblowing channels. Sportspersonship, confidence in resources and personal benefits were among the reasons that facilitate reporting doping misconduct. In addition, the divergence across countries in athletes’ beliefs related to doping whistleblowing suggested considering a cultural context for measures supporting doping whistblowing.